Learning Management System in Streamlining Learning through Seamless Learning Approach - Muchammad Eka Mahmud; Faizatul Widat; Anwar Fuadi (STAI Hubbulwathan Duri, 2021)
This study aims to analyze and understand the learning management system in learning effectively through a seamless learning approach at Islamic Elementary School Nurul Anwar. This research uses a qualitative case study approach. The data collection technique is done through observation, interviews, and documentation. At the same time, the data analysis was carried out through the stages of data display, data reduction, and concluding. The results of the study indicate that learning system management through a seamless learning approach at SD Islam Nurul Anwar in making learning effective is carried out; 1) User-friendly, 2) User Interface, 3) Parental involvement, 4) learning with an online learning system, outside the network (luring), and mobile teachers (guling). This research has implications for the importance of teachers in utilizing various existing and available resources to make their learning effective as optimally as possible.